Kersnikova Elza na poti od guvernante do poslančeve žene - Štuhec, Miran (Slavistična revija, 1998)
The central position in J. Kersnik's novels Ciklamen (The Cyclamen) and Agitator (The Agitator) is occupied by the German governess of the Boles' children Elza. She ambitiously and skilfuly controls the course of action; when necessary, she is also a ruthless plotter. Because of the fact that she is German, she assumes the role of an enemy of Slovene national interests. Because of her complexity, which at the end of The Cyclamen also involves a real human and love suffering, she is the most interesting character of the two novels and a medium for the reception of human, moral, and national-political life of Kersnik's ambient of a small town.
Keywords: Kernik, Janko; Kersnik, Janko: Agitator; Kersnik, Janko: Ciklamen; literarne študije; realizem; slovenska književnost